PERANCANGAN ALAT UKUR SISTEM MONITORING TERHADAP SUHU DAN KELEMBABAN TANAH BERBASIS IOT (INTERNET OF THINGS) DENGAN MENGGUNAKAN WEB MOBILE DI DESA MUARA KATI KABUPATEN MUSI RAWAS - Sobri, Ahmad; Nurdiansyah, Deni; Sunardi, Lukman (Jusikom : Jurnal Sistem Komputer Musirawas, 2023)
The purpose of this study was to determine the level of soil temperature and humidity in the village of Muara Kati, Musi Rawas Regency. The use of pH temperature and soil moisture measuring devices will have an impact on the crop yields of farmers in the Muara Kati sub-district and will also develop the community in cultivating other plantation crops if the soil impacts are good. The measurement tools used are arduino uno, usb cable, arduino IDE, Ethernet Shield, Twisted Pie cable, and a webmobile design system that uses UML, PHP and MySQL which helps this system. to make a temporary design for the system to be made, namely use cases, activity diagrams, sequence diagrams and also class diagrams. This system also displays a page that will detect the flow of the senor on the hardware and will display the level of soil acidity at soil pH and the temperature unstable in soil management and also good moisture content in the soil caused by unstable humidity.